Ванадий и никель в природных нефтях Азии, Африки, Европы, Северной и Южной Америки - Шнюков, Е.Ф.; Гожик, П.Ф.; Краюшкин, В.А.; Клочко, В.П.; Гусева, Э.Е.; Морозова, Р.М. (Видавничий дім "Академперіодика" НАН України, 2007)
In Africa, America, Asia, and Europe, many crude oils contain vanadium and nickel. Their concentrations are diverse, but the geochemically identical V/Ni ratios allow one to evidence the abyssal non-biotic origin of those crudes.